Sertifikasi Halal di Indonesia: Dari Voluntary menjadi Mandatory - Priantina, Anita; Mohd Sapian, Safeza (Tasyri' : Journal of Islamic Law, 2023)
Although Indonesia is the country with the largest Muslim population in the world, the halal industry faces several risks related to Shariah compliance. Following the enactment of Halal Assurance Law No. 33 of 2014, halal certification has become mandatory in Indonesia. Before, halal certificate was voluntary. The objective of this study is to discuss on the development of halal governance in Indonesia covering Halal Act, related government regulations and decrees from Ministries related to halal assurance and food security. In summary, the changes in halal governance in Indonesia from time to time is to support the halal assurance in the country. Therefore, it has to include all producers, including small and micro businesses.